Metacognitive Analogy Instruction: Effects on Students’ Reflective Thinking in Learning Biology - Recede, Reynald Alfred Auzana; Capati, Ariel Tacluyan; Yangco, Rosanelia Tablico; Castro, Mark Agustin (FKIP Universitas Lampung, 2020)
This study examined the effects of Metacognitive Analogy Instruction (MAI) on the students’ reflective thinking skills in Biology at the secondary level. A two-group pretest-posttest quasi experimental design was used to teach the control group using Non- Metacognitive Analogy Instruction (NMAI) which includes traditional way of teaching like lecture discussions, while the experimental group was taught using the Metacognitive Analogy Instruction. Results showed that students exposed to MAI improved better (M= 11.30) than those exposed to NMAI on the Habitual Action dimension (M= 10.09) of reflective thinking (p= 0.001) but the two groups had comparable performance (p= 0.42; 0.18; 0.09; & 0.10) on the Understanding (M= 14.40), Reflection (M= 12.47), and Critical Reflection dimensions (M= 12.73). The improvement of the MAI group in their overall reflective thinking skills scores particularly in the Habitual Action dimension could be attributed to the use of metacognitive analogies as part of the class instruction which required a considerable amount of focus and thinking. Hence, it is recommended that MAI be used for classroom instruction, curricular and instructional development, and teacher trainings to improve reflective thinking skills among students. Keywords: metacognition, metacognitive analogy, reflective thinking.DOI: http://dx.doi.org/10.23960/jpmipa/v21i1.pp12-21